LINGUOPRAGMATIC FEATURES OF THE FUNCTIONING OF AFFIXAL DERIVATIVES IN THE MEANING FIELD OF L. CAPUANA’S NOVEL “THE MARQUIS OF ROCCAVERDINE” - Okhrimenko, Valeriia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article focuses on linguopragmatic potential of affixal derivatives in the semantic field of the novel “The Marquis of Roccaverdina” by L. Capuana, one of the most prominent representatives of Italian verism. The semantic field of the verism novel “The Marquis of Roccaverdina” is based on polarized reference groups (associated with positive and negative characters) that implement the opposition “feudal lords – poor population”. The reference group has a field structure and includes the subject (character) as a representative of a social stratum, his place of residence, surrounding objects, landscape. The nucleus of the reference group is a subject (character) belonging to a higher vs. lower social stratum, the pre-nuclear zone – the place of residence, surrounding objects, landscape, the near periphery – the characteristics of the place of residence, surrounding objects, landscape. The nucleus of the reference group determines the spreading of the semantic space in a certain direction depending on the evaluation of the character and sets the direction of the typification of the conditions of meaning creation. The field structure is based on the degree of determinism, which decreases in the direction from the nucleus to the periphery. When characterizing negative characters (belonging to the class of feudal lords), affixal derivatives with augmentative suffixes, pejorative suffixes, negative prefixes are used in the pre-nuclear zone, and on the near periphery – descriptors indicating the size of cultural artifacts and household items, which correlates with the greatness of the marquis and his family. Descriptors often function as epithets. To describe the landscape and natural phenomena surrounding negative characters, the author often uses the stylistic device of personification, and natural phenomena are correlated with their character traits and mental state. In the microcontext, lexical units of negative evaluation are used. In the speech of negative characters, deictics with the function of referent substitution are used, which reinforce the meaning of affixal derivatives with a negative prefix or pejorative suffixes. When characterizing positive characters (belonging to a lower class) affixal derivatives with diminutive suffixes are used in the pre-nuclear zone, descriptors indicating the small size of artifacts and household items are used in the near periphery; in themicro context, lexical units are used to denote impersonality. To describe the landscape and natural phenomena surrounding positive characters, the author often uses the stylistic device of personification, while natural phenomena are perceived as threatening and correlated with their state of depression and helplessness. The polarization of reference groups implementing the opposition "feudal lords – poor stratum of the population" is manifested in the semantic relation of contradiction, which include affixal derivatives and their descriptors. The semantic relations of contradiction are revealed in the stylistic device of antithesis used not only at the level of single phrase, but also at the transphrastic and textonomic level. The identification of the linguopragmatic potential of affixal derivatives is possible due to imposition of semantic connections in the semantic space of the novel. The author’s choice of affixal derivatives is pragmatically conditioned. ____________ References: • Manakin, V. M. Zistavna leksykolohiya (Kyiv: Znannya, 2004), 326. • Okhkimenko, V. I. «Ontolohiya ta hnoseolohiya katehoriyi modal’nosti v italiys’kij movi» (dis. d-ra filol nauk, Kjiv, 2012), 612. • Seliverstova, A. O. Linhvoprahmatychni osoblyvosti funktsionuvannya afiksalʹnykh deryvativ u literaturi veryzmu (na prykladi romanu L. Kapuany “Il Marchese di Roccaverdina” Problemy semantyky, prahmatyky ta kohnityvnoyi linhvistyky 43 (2023): 81-91. • Znak. Dyskurs. Antolohiya svitovoyi literaturno-krytychnoyi dumky XX st., za red. mariyi Zubryts’koyi (Lviv: Litopys, 1996), 633. • Adriano, Alienazione, nevrosi e follia: esiti della ricerca scientifica nella narrativa italiana tra Otto e Novecento (Sassari: Università di Sassari, 2009), 297. • Fillmore, Ch. Frame semantics and the nature of language «Annals of the New York Academy of Sciences: Conference on the Origin and Development of Language and Speech» 280 (1976): 20-32. • Jochimsen, M. Luigi Capuana e Federico de Roberto e il fine del verismo italiano (Leipzig: Verlag, 2010), 20. • Kay, P., Kempton, W. What is the Sapir-Whorf Hypothesis? New Series 86 (1): 65-79. • Ledda, C. La Ricerca della lingua nelle novelle del primo Capuana (1867/1889) (Sassari: Università degli studi di Sassari, 2011), 317. • Micheli, M.S. La formazione delle parole. Italiano e altre lingue (Roma: Carocci Editore, 2020), 240. • Muoio, I. Tra il naturalismo di ‘costì’ e il verismo ‘di qui’. «Incontri: Rivista europea di Studi Italiani» 33 (2): 52-64. • Capuana, L. Il marchese di Roccaverdina (Milano; Mondadori, 2010), 309.